2016
DOI: 10.1002/mds.26624
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeropathies and pathogenesis of Alzheimer and Parkinson's diseases

Abstract: The term oligomeropathies defines the neurodegenerative disorders associated with protein misfolding, where small soluble aggregates (oligomers 4-200 KDa) are the cause of neuronal dysfunction and are responsible for spreading the pathology. The ability of these soluble β-sheet conformers to induce neuronal damage has been investigated in direct challenge with the monomeric and fibrillary structures, showing that only the oligomeric species affected the neurons. β amyloid oligomers were initially purified from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 156 publications
(264 reference statements)
2
77
0
1
Order By: Relevance
“…It has been observed that mutations causing or exacerbating these proteinopathies increase, in many cases, the protein propensity to form aggregates, thus linking the formation of protein deposits in the brain and the degeneration of the nervous system [55]. Also, there are mounting evidences for a major contribution of oxidative stress in the pathology of these disorders [56], [57], with clear indications of oxidative damage to lipids, proteins and DNA in patient’s post-mortem brains [19], [24], [26], [27]. The connection between protein aggregation propensity and oxidative stress has been demonstrated in models of HD, where the aggregation tendency of the protein is determined by the length of the poly(Q) expansion, longer poly(Q) stretches being more aggregation-prone and inducing higher ROS production than shorter segments in wild type sequences [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that mutations causing or exacerbating these proteinopathies increase, in many cases, the protein propensity to form aggregates, thus linking the formation of protein deposits in the brain and the degeneration of the nervous system [55]. Also, there are mounting evidences for a major contribution of oxidative stress in the pathology of these disorders [56], [57], with clear indications of oxidative damage to lipids, proteins and DNA in patient’s post-mortem brains [19], [24], [26], [27]. The connection between protein aggregation propensity and oxidative stress has been demonstrated in models of HD, where the aggregation tendency of the protein is determined by the length of the poly(Q) expansion, longer poly(Q) stretches being more aggregation-prone and inducing higher ROS production than shorter segments in wild type sequences [58].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of PI in neurodegenerative diseases has been traditionally assumed to reflect the insufficiency of this first line of defence [15]. However, it was proposed later that the formation of PI can instead act as a protective strategy [16], [17], triggering an intense dispute on the specific protein species responsible for the cellular damage [18], [19]. It has been suggested that earlier aggregation intermediates, such as oligomeric and/or protofibrillar assemblies, would disrupt the cellular homeostasis by promoting aberrant interactions with different cellular components [20], including the protein quality surveillance machinery, whereas the formation of inclusions at specific cellular sites might be indeed a detoxifying mechanism against the presence of these promiscuous species [17], [21].…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the accumulation of aberrant proteins that can organize into aggregates that are potentially toxic to the cell [7]. Protein aggregates are extensively studied in the context of neurodegenerative diseases [8] [9] [10], however only few studies have so far focused on protein aggregation during natural aging [11] [12]. Therefore, specific protein aggregates not associated to a specific disease can be potential biomarkers of physiological aging.…”
Section: Introductionmentioning
confidence: 99%
“…Although the abnormal aggregation of α‐syn plays a critical role in PD pathogenesis, the exact pathogenic α‐syn species remain undefined . Several studies have demonstrated that amyloid oligomers, but not mature amyloid fibrils, are the neurotoxic species . Therefore, several studies have investigated the potential role of CSF α‐syn as a putative biomarker for PD.…”
mentioning
confidence: 99%